Safety and economic analysis of the EasyEndo disposable endoscopic cutting and stapling device for VATS lobectomy or segmentectomy in lung cancer patients: a retrospective study - Han, Ziyang; Lu, Jieming; Chen, Shuchen; Yu, Shaobin; Zhang, Peipei; Kang, Mingqiang (Frontiers in Oncology, 2023)
Objective: The aim of this retrospective study was to investigate the safety and economic aspects of using the EasyEndo disposable endoscopic cutting and stapling device for video-assisted thoracoscopic surgery (VATS) lobectomy or segmentectomy in patients with lung cancer. The choice between the two staplers was influenced by changes in our hospital's procurement policy; Johnson EC45A was used before January 2022 and was then replaced by the EasyEndo stapler. Methods: We reviewed and analyzed consecutive patients with lung cancer who underwent VATS segmentectomy from March 2021 to December 2022. Inclusion criteria included patients with suspected non-small cell lung cancer (NSCLC) who were eligible for surgical resection. The surgical procedures were performed using either the EasyEndo or Johnson EC45A staplers. Intraoperative variables, postoperative outcomes, and cost analysis were compared between the two groups. Results: A total of 1556 patients were included in the study, with 775 patients in the Control group and 781 patients in the EasyEndo group. There were no significant differences in patient characteristics between the two groups. Intraoperative variables, including blood loss, blood transfusion, and operation time, showed no significant differences between the groups. Postoperative outcomes, such as hospital stay, drainage tube placement time, and incidence of complications, were also comparable between the two groups. However, there was a significant difference in the cost of stapler usage, with the EasyEndo group showing a lower cost compared to the Control group. Conclusion: The EasyEndo disposable endoscopic cutting and stapling device demonstrated comparable safety and effectiveness to the Johnson EC45A stapler in VATS segmentectomy for lung cancer patients. Moreover, the use of the EasyEndo stapler resulted in cost savings, indicating its potential economic benefits for healthcare institutions. Keywords: lung cancer, video-assisted thoracoscopic surgery, EasyEndo, stapler, safety, economic analysis.